17-alpha hydroxyprogesterone caproate for the prevention of recurrent preterm birth among singleton pregnant women with a prior history of preterm birth: a systematic review and meta-analysis of six randomized controlled trials - Saeed Baradwan (Korean Society of Obstetrics and Gynecology, 2021)
To perform a systematic review and meta-analysis of all randomized controlled trials (RCTs) that investigated the clinical benefits of 17-alpha hydroxyprogesterone caproate (17OHPC) in the prevention of recurrent preterm birth (PTB) among singleton pregnant women with a previous history of PTB. We searched four major databases up till April 2021 and assessed the risk of bias in the included studies. We meta-analyzed various maternal-neonatal endpoints (n=18) and pooled them as mean difference or risk ratio (RR) with 95% confidence interval (CI) using the random-effects model. Six RCTs met the inclusion criteria, comprising 2,573 patients (17OHPC=1,617, control=956). RCTs revealed an overall low risk of bias. The rates of PTB <35 weeks (n=5 RCTs; RR, 0.77; 95% CI, 0.63–0.93; P=0.008), PTB <32 weeks (n=3 RCTs; RR, 0.68; 95% CI, 0.51–0.91; P=0.009), neonates with low birth weight (<2.5 kg) at delivery (n=3 RCTs; RR, 0.63; 95% CI, 0.5–0.79; P<0.001), and neonatal death (n=4 RCTs; RR, 0.41; 95% CI, 0.20–0.84; P=0.02) were significantly reduced in the 17OHPC group compared with the control group. Moreover, 17OHPC treatment correlated with a significantly decreased rate of retinopathy (n=2 RCTs; RR, 0.42; 95% CI, 0.18–0.97; P=0.004). However, there were no significant differences in the rates of neonatal intensive care unit admission, cesarean delivery, and other preterm-related complications between both the groups. Among singleton pregnant women with a prior history of PTB, 17OHPC may favorably decrease the risks of recurrent PTB and reduce the rate of neonatal death.